Character Education in Schools: A Comparison of Indonesian and Japanese Policies - Arina, Ida; Deni Darmawan, Deni; Buriyeva, Kibrio; Ximmataliyev, Dostnazar (LPPM Institut Pendidikan Nusantara Global, 2025)
Character education in schools is an important concern in improving the quality of education in Indonesia. By comparing policies with Japan, we can understand the differences in approaches and strategies in developing student character. Indonesia and Japan implement character education in the education system to form a generation with good character and preserve important cultural and traditional values ​​in society. Character education plays an important role in maintaining and continuing cultural heritage, as well as strengthening traditional values ​​in society. Thus, character education becomes an effective means to maintain and preserve unique cultural identities and traditions. Character education in Indonesia and Japan has different backgrounds. In Indonesia, character education was introduced as an effort to improve the quality of education and form students with good character. The Indonesian government has issued various policies to support the implementation of character education in schools. Meanwhile, Japan has had a strong tradition of character education for a long time, with an emphasis on values ​​such as discipline, hard work, and responsibility. Character education is an important aspect of the education system that aims to shape students into individuals with noble character, integrity, and positive contributions to society. In recent years, character education has become a focus of attention in various countries, including Indonesia and Japan. The two countries have different approaches in implementing character education in schools. This article will compare character education policies in Indonesia and Japan, and analyze the advantages and disadvantages of each approach